Acidovorax citruli: genetic analyses and protocol for its detection in seeds - Silva, Gustavo Mateus da (2016)
Bacterial fruit blotch of cucurbits (BFB), caused by the seed borne Gramnegative bacterium Acidovorax citrulli is a serious threat to cucurbit industry worldwide. Since late 1980`s after devastating outbreaks in watermelon fields in southern United States, BFB has spread worldwide and has been reported in other cucurbit crops such as melon, pumpkin, cucumber and squash. To date, there is evidence for the existence of at least two genetically and pathogenically distinct populations of A. citrulli. In Brazil, the first report of BFB was in 1991, in a watermelon field in São Paulo. Although widespread in the country, BFB has been a major problem to melon production. More precisely, BFB has caused significant yield losses to melon production in northeastern Brazil, which concentrates > 90% of the country`s melon production. Despite the management efforts and the recent advances in A. citrulli research, BFB is still a continuous threat to the cucurbit industry, including seed producers, growers and transplant nurseries. To better understand the population structure of A. citrulli strains in Brazil, and to provide a basis for the integrated management of BFB, we used pulsed-field gel electrophoresis (PFGE), multilocus sequence analysis (MLSA) of housekeeping and virulence-associated genes and pathogenicity tests on different cucurbit seedlings to characterize a Brazilian population of A. citrulli strains from different hosts and regions. Additionally, we conducted for the first time a comparative analysis of the A. citrulli group I and II population at genomic level and showed that these two groups differ on their genome sizes due to the presence of eight DNA segments, which are present in group II and absent in group I genomes. We also provide the first evidence to suggest that temperature might be a driver in the ecological adaptation of A. citrulli populations under nutrient-rich or -depleted conditions. Finally, in order to improve the routine detection of A. citrulli on melon seedlots, we designed a new primer set that is able to detect the different Brazilian haplotypes, thus minimizing the risk of false-negatives on PCR-based seed health testing.